2010
DOI: 10.2109/jcersj2.118.202
|View full text |Cite
|
Sign up to set email alerts
|

Micro gas sensor assembly of tin oxide nano-particles by a capillary micro-molding process

Abstract: This paper reports a micro gas sensor assembled with tin oxide, SnO2, nano-powders. The micro gas sensors are fabricated by a modified micro molding in capillary (MIMIC) technique using an ethanol suspension with 2.0 vol% SnO2 nano-powders. A micro pattern is formed as a set of parallel lines 23 μm in width and 1.2 μm in depth. The micro pattern is heat treated at 300°C for 5 h. The micro-sensor was able to detect ethanol gas by measuring the electrical resistance of the tin oxide a glass tube furnace. When et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Patterned films are the basis of many applications such as ceramic gas sensors [1] [2] [3] [4] Micro-ElectroMechanical Systems [5], and complex 3D microelectronic components based on the Low Temperature Cofired Ceramics (LTCC) technology. In practice, challenges arise from the co-sintering of these layered systems due to the geometrical constraint imposed by adjacent layers that densify at a different rate, or not at all in the case of rigid substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Patterned films are the basis of many applications such as ceramic gas sensors [1] [2] [3] [4] Micro-ElectroMechanical Systems [5], and complex 3D microelectronic components based on the Low Temperature Cofired Ceramics (LTCC) technology. In practice, challenges arise from the co-sintering of these layered systems due to the geometrical constraint imposed by adjacent layers that densify at a different rate, or not at all in the case of rigid substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The master is prepared by any other lithographic technique which defines the smallest topological feature required. There are several techniques which enable the transfer of a pattern with PDMS molds [20]: microcontact printing (μCP) [21], micromolding in capillaries (MIMIC) [22], microtransfer molding (μTM) and minor modifications of these. The techniques used in this study are schematically demonstrated in figure 1.…”
Section: Deposition Techniquesmentioning
confidence: 99%
“…Many engineering applications require ceramic films with finite lateral dimensions. Examples range from micro‐electro‐mechanical systems and microfluidics to ceramic gas sensors . Despite their widespread use in the industrial context and several unsolved problems such as cracking and delamination, little research on the sintering behavior of sintering stripes bonded to rigid substrates has been carried out so far.…”
Section: Introductionmentioning
confidence: 99%